Neo-tanshinlactone D-ring modified novel analogues induce apoptosis in human breast cancer cell via DNA damage. Issue 1 (1st January 2017) - Banerji, Biswadip; Killi, Sunil Kumar; Katarkar, Atul; Chatterjee, Satadru; Tangella, Yellaiah; Prodhan, Chandraday; Chaudhuri, Keya
Graphical abstract: Abstract: Neo-tanshinlactone (NTL) a natural product is known for its specificity and selectivity towards the breast cancer cells. By NTL D-ring modification approach, 13 new analogues were synthesized (1A –1M ). Among them1J showed the best anticancer activity in MCF-7 (ER+, PR+/−, HER2−), SKBR3 (ER−, PR−, HER2+) and MDA-MB-231 (ER−, PR−, HER2−) cells lines with IC50 value 11.98 nM, 23.71 nM, and 62.91 nM respectively.1J showed minor grove binding interaction with DNA at AT-rich region and induced DNA double strand breaks (DDSBs). This had triggered several key molecular events involving, activation of ATM, Chk2 and p53, reduction in mitochondrial potential (Δ ψ m ) leading to caspase-3 and PARP cleavage mediated apoptosis. These results along with other biochemical studies strongly suggest that novel NTL analogue1J caused DNA cleavage mediated apoptosis in the breast cancer cells and this may serve as potential lead for future breast cancer treatment.